1999
DOI: 10.1116/1.591012
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of roughness in chemically amplified resists using percolation theory

Abstract: Articles you may be interested inProbabilistic gel formation theory in negative tone chemically amplified resists used in optical and electron beam lithography J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
(5 reference statements)
0
14
0
4
Order By: Relevance
“…Because of its importance in the last few years, several publications discuss the problem of roughness. [1][2][3][4][5][6][7][8][9] Surface roughness ͑SR͒ appears after the spin coating of the photoresist film, while line edge roughness ͑LER͒ appears after the development of the microstructure. However, the two phenomena are closely related.…”
Section: Framework For Sr and Ler Studiesmentioning
confidence: 99%
“…Because of its importance in the last few years, several publications discuss the problem of roughness. [1][2][3][4][5][6][7][8][9] Surface roughness ͑SR͒ appears after the spin coating of the photoresist film, while line edge roughness ͑LER͒ appears after the development of the microstructure. However, the two phenomena are closely related.…”
Section: Framework For Sr and Ler Studiesmentioning
confidence: 99%
“…This is done in Fig. 24,35 Finally, it was observed that LER and SR after the development simulation show a decrease in their magnitude in all doses when the PAG concentration increases. At low doses many small clusters exist in the lattice and the developer can easily surround them and remove them.…”
Section: Surface and Line-edge Roughnessmentioning
confidence: 83%
“…Stockmayer 14 analyzed the work of Flory in great detail and managed to calculate the molecular weight distribution up to the gel point. [23][24][25][26][27] In this article a modeling methodology is developed for negative tone CARs with low initial polymerization length based on the simulation of microscopic processes during PEB that lead to the gel formation and the appearance of a ''latent'' surface and line-edge roughness in the resist profile prior to development. 15 Eichinger and Akgiray 16 give a comprehensive review of the methods used to describe polymer network formation.…”
Section: Introductionmentioning
confidence: 99%
“…It takes into account the molecular structure of the photoresist, the photoacid generator presence, its initiation, diffusion and reaction to create deprotected sites as well as the dissolution of the exposed areas using a quasistatic fast dissolution algorithm [32][33][34]. Excellent process simulation and experimental studies have also appeared in the literature for the process effects on LER, such as aerial image contrast [35][36][37], shot noise [38], development process [39][40][41][42][43], lithographic process conditions [44][45][46][47][48], lithographic materials [32,33,[49][50][51][52][55][56][57][58][59] and others. Our simulation results are consistent with these studies.…”
Section: Line Edge Roughness (Ler) Resulting From Nanolithography Andmentioning
confidence: 99%